Estudio de factibilidad para la creación de una cooperativa multiactiva de tenderos en el municipio de Armenia Quindío (2007)
At present, the solidary economy sector is acquiring an important dynamic, becoming an alternative of efficient business organization with capacity to generate economic growth and social welfare. Within the legal framework Law 454 of 1998, solidarity economy is defined as a "socioeconomic, cultural and environmental system formed by the set of social forces organized in associative forms identified by self-management practices of solidarity, democracy, humanism, non-profit for the integral development of the human being as subject, actor and purpose of the economy "(article 2). This is why in order to promote and strengthen the sector, the present project is proposed and cooperatives are a form of economic solidarity organization; capable of generating well-being and development for its affiliates, as well as what it says that cooperatives can work for the sustainable development of the communities of their territorial scope, based on the policies approved by the administrative entities. The result of this study poses how the segmentation of the customer market, according to the geographic location in the city, has survived the chain of stores, and in turn, how the conservative attitude regarding the growth of the organization has possible to stay.